Elements of Romanticism in Selected Works of Muriel Spark - Jelínková, Simona (Univerzita Pardubice, 2014)
This bachelor thesis deals with the elements of Romanticism, namely the Grotesque and the Gothic, in three novels by Muriel Spark Memento Mori, The Ballad of Peckham Rye and The Prime of Miss Jean Brodie. In the theoretical part of this thesis, the characteristics of Romanticism and the above mentioned elements are defined. The analysis of the three novels illustrates Muriel Spark's usage of the elements of Romanticism.
Prvky romantismu ve vybraných dílech Muriel Spark
Keywords: grotesque; gothic; Memento Mori; Ballad of Peckham Rye; Prime of Miss Jean Brodie; groteskno; gotično; Memento Mori; Balada z předměstí; Nejlepší léta slečny Jean Brodiové